2004
DOI: 10.1073/pnas.0401982101
|View full text |Cite
|
Sign up to set email alerts
|

A truncated aminoacyl–tRNA synthetase modifies RNA

Abstract: Aminoacyl-tRNA synthetases are modular enzymes composed of a central active site domain to which additional functional domains were appended in the course of evolution. Analysis of bacterial genome sequences revealed the presence of many shorter aminoacyl-tRNA synthetase paralogs. Here we report the characterization of a well conserved glutamyl-tRNA synthetase (GluRS) paralog (YadB in Escherichia coli) that is present in the genomes of >40 species of proteobacteria, cyanobacteria, and actinobacteria. The E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 40 publications
1
80
0
4
Order By: Relevance
“…2004;Salazar et al 2004). However, glutamate is not esterified to the normal aminoacylation position at the tRNA's 3Ј-terminal adenosine, but is attached to the hypermodified nucleoside queuosine located in the first position of the tRNA Asp anticodon (Salazar et al 2004). Thus, this aatRNA synthetase fragment contributes to nucleotide modification of tRNA, further broadening the range of functions thus far attributed to synthetase paralogs.…”
Section: Synthetase-like Proteinsmentioning
confidence: 99%
“…2004;Salazar et al 2004). However, glutamate is not esterified to the normal aminoacylation position at the tRNA's 3Ј-terminal adenosine, but is attached to the hypermodified nucleoside queuosine located in the first position of the tRNA Asp anticodon (Salazar et al 2004). Thus, this aatRNA synthetase fragment contributes to nucleotide modification of tRNA, further broadening the range of functions thus far attributed to synthetase paralogs.…”
Section: Synthetase-like Proteinsmentioning
confidence: 99%
“…Conscription of the adenylylation reaction catalyzed by these enzymes is not without precedent. Truncated paralogues of aaRS enzymes are involved in diverse noncanonical functions, including tRNA modifications (27), and biosynthesis of amino acids and other metabolites (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies confirmed YadB as a structural analogue of the catalytic core of GluRS that has retained the ability to activate glutamate (11), albeit without the need for tRNA binding that characterizes GluRS (12). Closer examination revealed that YadB does not attach activated glutamate to either tRNA Gln or tRNA Glu (11), but instead to tRNA Asp (9,13). Although the latter report by Dubois et al (13) in this issue of PNAS provided unequivocal evidence for the surprising aminoacylation of tRNA Asp , it left unanswered the more vexing question of what function, if any, this apparent heterologous aminoacylation serves in vivo.…”
mentioning
confidence: 99%
“…The surprising answer to the question of YadB's function is provided by the work of Salazar et al (9). In addition to confirming what was reported concerning YadB (11, 13), Salazar et al establish a truly surprising fate for the amino acid in YadB aminoacylation: rather than being transferred to the 3Ј end of the tRNA, the glutamate becomes attached to the hypermodified nucleoside queuosine (Q) at the first anticodon position, leading to the formation of glutamyl-Q (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation